2017
DOI: 10.1097/ajp.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasonography-guided Bilateral Intercostal Nerve Blocks and Conventional Patient-controlled Intravenous Analgesia for Pain Control After the Nuss Procedure in Children

Abstract: Objectives:Patients experience severe pain after pectus excavatum (PE) surgery. The aim of this prospective, randomized study was to compare analgesic effects of ultrasonography-guided bilateral intercostal nerve blocks (UG-ICNBs) with those of conventional patient-controlled intravenous analgesia (PCIA) on acute pain after the Nuss procedure for PE repair in children.Methods:A prospective randomized study was performed in children with PE who were scheduled for the Nuss procedure. Participants were randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…[3][4][5][8][9][10] Several studies have shown that the ICNB improves postoperative pulmonary functions, while decreasing opioid consumption, and reduces associated complications by providing improved postoperative pain control. [4,[10][11][12][13][14][15][16] Similar to our study, Barr et al [4] found reduced pain scores and total opioid consumption in the patients where they performed operations with parasternal ICNB for pain management after adult cardiac surgery. Lukosiene et al [17] also conducted a study in pediatric patients undergoing minimally invasive thoracic surgery where they evaluated the efficacy of ICNB on acute pain management after the Nuss procedure.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…[3][4][5][8][9][10] Several studies have shown that the ICNB improves postoperative pulmonary functions, while decreasing opioid consumption, and reduces associated complications by providing improved postoperative pain control. [4,[10][11][12][13][14][15][16] Similar to our study, Barr et al [4] found reduced pain scores and total opioid consumption in the patients where they performed operations with parasternal ICNB for pain management after adult cardiac surgery. Lukosiene et al [17] also conducted a study in pediatric patients undergoing minimally invasive thoracic surgery where they evaluated the efficacy of ICNB on acute pain management after the Nuss procedure.…”
Section: Discussionsupporting
confidence: 83%
“…We also found improved pain and sedation scores in Group 1 (ICNB group) compared to Group 2 (intravenous group) with less morphine consumption. Luo et al [14] also demonstrated that the ICNB was more effective than patient-controlled intravenous analgesia in pediatric patients undergoing the Nuss procedure during the acute postoperative period. According to our study results, ICNB provided better analgesia for pain control after ASD repair performed with mini-thoracotomy.…”
Section: Discussionmentioning
confidence: 98%
“… 198 , 199 Two studies investigated the effectiveness of regional anesthesia in providing postoperative pain in children undergoing the Nuss procedure. 29 , 65 One study compared ultrasound-guided bilateral intercostal nerve blocks with intravenous analgesia for postoperative analgesia. The postoperative pain scores (Faces Pain Scale-Revised, FPS-R) in the first 6 hours were significantly decreased in the nerve block group compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The prolonged analgesic duration of SAPB and Pecs II blocks explain the much lower, almost one-third post-operative rescue fentanyl requirement in the former groups compared to the ICNB group [ Table 3 ]. [ 19 20 ] This can be attributed to the elevated systemic absorption and rapid clearance of the drug from the highly vascular intercostal bed[ 21 22 ] whereas the deposition of the local anaesthetic (LA) drug in a myofascial plane of interest is expected to more selectively block the higher-order ramifications of the branches of the intercostal nerves. [ 8 23 24 25 ] In addition, other analgesics such as non-steroidal anti-inflammatory drugs were avoided in all the study participants, particularly given a cardiac surgical setting where the former can potentially predispose to postoperative bleeding and/or acute-kidney injury.…”
Section: Discussionmentioning
confidence: 99%